Qur'an And Al-Hadits Model-Based Education In Increasing Islamic Civilization - Zakariya, Din Muhammad (Prodi Pendidikan Agama Islam - Fakultas Agama Islam ( FAI ), 2018)
Abstract This study aimed to explore how educational models that can realize high-emergence of Islamic civilization; how civilization produced by education based on the revelation of the Qur'an and Al-Hadits); and what happens when a civilization based education override revelation (Al-Quran and Al-Hadits). This study is intended as an exploration efforts and the transformation of science into the Islamic education system is an integral and operationally. This type of research is the approach of the literature; the data collection method: the method of documentation and observation method, while the method of the interview as a method of investigation to collect data related to this study. Analysis of the data used in this study is a non-statistical analysis. The research result is concluded: first,the emergence of education that can realize the high Islamic civilization is education based on revelation; second,civilization produced by education based on revelation (Al-Quran and Al-Hadits) is a civilization which brings benefit in this world and happiness in the hereafter. Third,when civilization based education override revelation (Al-Quran and Al-Hadits) then there is the deterioration and destruction. Keywords: education, civilization of Islam, the Qur'an and al-Hadits